2020
DOI: 10.1007/s13304-020-00916-1
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and updated network meta-analysis comparing open, laparoscopic, and robotic pancreaticoduodenectomy

Abstract: The treatment of periampullary and pancreatic head neoplasms is evolving. While minimally invasive Pancreaticoduodenectomy (PD) has gained worldwide interest, there has been a debate on its related outcomes. The purpose of this paper was to provide an updated evidence comparing short-term surgical and oncologic outcomes within Open Pancreaticoduodenectomy (OpenPD), Laparoscopic Pancreaticoduodenectomy (LapPD), and Robotic Pancreaticoduodenectomy (RobPD). MEDLINE, Web of Science, PubMed, Cochrane Central Librar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 85 publications
2
22
0
Order By: Relevance
“…Hence, in accordance with other data already reported in literature, the most relevant consequence of the better post-operative course after RPD positively impacting on costs was the significantly shorter LoS [4,26,27,33,34]. Indeed, despite the minimal differences in clinical outcomes between the two groups, the stay of the open group was meaningful 6 days longer, likewise or even better to data reported by some authors in series showing no differences in term of overall post-operative complications between OPD and RPD [35,36].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Hence, in accordance with other data already reported in literature, the most relevant consequence of the better post-operative course after RPD positively impacting on costs was the significantly shorter LoS [4,26,27,33,34]. Indeed, despite the minimal differences in clinical outcomes between the two groups, the stay of the open group was meaningful 6 days longer, likewise or even better to data reported by some authors in series showing no differences in term of overall post-operative complications between OPD and RPD [35,36].…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, in the last years, RAS has been increasingly diffused for different surgical procedures, including pancreatic surgery, mostly for distal pancreatectomy but also for PD. Considering the clinical outcomes, RPD represents a remarkable application of minimally invasive surgical technology, and some studies have shown favorable results if compared to the open approach [25][26][27]. Hence, the technical advantages of robotic systems should theoretically allow the expansion of the adoption of minimally invasive approach in the field of pancreatic surgery [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, all of these studies were institutional series with small sample sizes. Corresponding findings have also been seen in other complex operations such as major hepatic resections [ 13 , 14 ], pancreatoduodenectomies [ 15 ], and esophagectomies, [ 16 ] where minimally invasive approaches, including robotic and laparoscopic surgery, were found to have similar perioperative outcomes compared to traditional open surgery.…”
Section: Introductionsupporting
confidence: 58%
“…And with the development of technology and minimally invasive tendency in medicine, minimally invasive pancreaticoduodenectomy, especially total laparoscopic pancreaticoduodenectomy (tLPD) is not out of this way. Recent systematic reviews showed that LPD was superior against open PD in aspects of inoperative blood transfusion, wound and pulmonary infection, and shorter hospital stays; and there are no differences of relevant postoperative pancreatic stula (POPF), severe complications, postoperative mortality, retrieved lymph nodes (LNs), and R0-resection rate [3,4]. However, to achieve the safety and effectiveness, they also recommended that LPD should be proceed by surgeons with expertise and through learning curve in high-volume centers [3,4].…”
Section: Introductionmentioning
confidence: 99%